Efektivitas Nano Guano dan Eco-Enzyme terhadap Pertumbuhan Jagung (Zea mays L.) dan Serapan Fosfor di Tanah Inceptisol - Yuliani, Farida; Anwar, Khairul; Fairuzzia, Fazat; Farhana, Maulina (Jurnal Pertanian, 2024)
This study aims to determine the effect of nano guano and eco-enzyme application on corn (Zea mays L.) cultivated in Inceptisol soil. The research method employed a Complete Randomized Block Design (RAKL) factorial with the first factor being nano guano dosage: D1 (0 kg/ha), D2 (50 kg/ha), D3 (75 kg/ha), and D4 (100 kg/ha). Meanwhile, the second factor was eco-enzyme concentration: E1 (0 ml/L), E2 (1 ml/L), and E3 (2 ml/L). Each combination was repeated three times in block form. The data obtained were then analyzed using ANOVA and further tested with LSD (Least Significant Difference) at a 5% level. The results of the study indicate that 1 inceptisol soil is classified as having low fertility, there is no significant effect on the plant height and number of leaves of corn plants treated with nano guano, and eco-enzyme application influences the height and number of leaves of corn plants at 3 and 4 week after planting.